Hubungan Perilaku Asertif dengan Kenalan Remaja dan Masalahanya di SMAN 2 Masbagik - LL. Zihnan Munir (FONDATIA, 2019)
This study aims to determine the relationship of assertive behavior with juvenile delinquency and the problem in students of SMAN 2 Masbagik. The research design used is descriptive and correlational. The research population was 170 SMAN 2 Masbagik students. The research sample was 119 people, used by random sampling technique. The research instrument used is the psychological scale. The data analysis technique used is descriptive analysis and product moment correlation analysis. Based on the study of the assertive behavior of respondents included in the high category that is 73.95%. Most of the juvenile delinquency of respondents who fall into the category is quite 64.71%. Correlation analysis results obtained by the magnitude of the correlation coefficient of -0.211. The correlation test results showed that the rxy obtained was -0.211 while the r table with N = 119 was 0.176. Because the value of r arithmetic> r table (-0.211> 0.176) then there is a negative relationship between certive behavior and juvenile delinquency. Effective contribution of assertive variables is 4.45% of juvenile delinquency in class XI students of SMAN 2 Masbagik. The results give students the opportunity to express what students want to express without shame, students should always be assertive in their stance, honest with themselves and honest with others, always responsible for what they have done, know themselves and also have high self confidence